Avaliação do uso de taninos comerciais em vinho "merlot" na região da campanha - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The work was conducted with ‘Merlot’ grapes from the city of Dom Pedrito, region of the Campanha Gaucha - RS, which gets highlighted in production of wines in the country, for its good adaptation to different regions. The cultivate usually gives very good wines, because the field can achieve both phenolic ripeness as sugars, however in certain year crops, where the climate is not as favorable may present problems as any other cultivar, but the taste evaluation was no difference in round tannins and also in variable overall evaluation, especially in treatments of mix tannins. Currently, there are strategies that can be used in the field and within the industry to improve the quality of the products, even if they originate in good yields, because with the use of these tools is achieved a differentiation in the same market level. In this context, this study aimed to study the application of commercial tannins of different origins in ‘Merlot’ wines as well as evaluation of their performance in the sensory and physicochemical characteristics. The tannins were applied soon after Descube wine comprises a total of 10 treatments, 01 – without tannins adictions, 02 – grape tanines 15 g.HL‾¹, 03 – quebracho tanines 40 g.HL‾¹, 04 - oak tanines 20 g.HL‾¹, 05 – combination of grape tanines 15 g.HL‾¹ + quebracho tanines 40 g.HL‾¹, 06 – combination of grape tanines 15 g.HL‾¹ + oak tanines 20 g.HL‾¹, 07 – grape tanine with polysaccharide 30 g.HL‾¹, 08 – grape tanine with polysaccharide 60 g.HL‾¹, 09 - combination grape tanine with polysaccharide 60 g.HL‾¹ + oak tanines 20 g.HL‾¹ e 10 - tanine with polysaccharide 60 g.HL‾¹ + quebracho tanine 40 g.HL‾¹. After one and a half year were performed analyses of the experiment by wine scan. (Infrared Fourier transform spectroscopy). The results were interesting, including variable color, total polyphenols and tannins have been influenced, showing statistically significant differences, these results were expected, because these are the most influential variables by tannins. In the sensorial analysis, tannins printed interesting differences. From this perspective, it can be said that the use of tannins contributes very effectively to the final quality of the wines
Keywords: Vinho; Qualidade; Taninos; Merlot; wine; Quality; tannins; CNPQ::CIENCIAS EXATAS E DA TERRA